2012
DOI: 10.1039/c2ee21574h
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable carbon nanoparticles designed for downhole hydrocarbon detection

Abstract: Sulfated polyvinyl alcohol functionalized carbon black, stable under high temperature and high salinity conditions, efficiently carries a hydrophobic compound through a variety of oil-field rock types and releases the compound when the rock contains hydrocarbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…The use of nanoparticles (NPs) for enhanced oil recovery (EOR) has received intensive attention since 2008, and much work has been conducted that can be generally categorized as: (i) the development of 'contrast-agent' type NPs to improve the detection limitation of seismic and EM techniques for better reservoir characterization [1][2][3]; (ii) the use of NPs as property modifiers, i.e., to alter rock wettability and interfacial tension at the oil/water interface in order to increase oil recovery rates [4][5][6][7]; and (iii) the use of NPs for conformance control such as nanoparticle-stabilized emulsions, and gelation materials to block the easy flow paths [8,9]. All these applications require nanoparticles to transport long distances in reservoir rocks with minimal retention.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanoparticles (NPs) for enhanced oil recovery (EOR) has received intensive attention since 2008, and much work has been conducted that can be generally categorized as: (i) the development of 'contrast-agent' type NPs to improve the detection limitation of seismic and EM techniques for better reservoir characterization [1][2][3]; (ii) the use of NPs as property modifiers, i.e., to alter rock wettability and interfacial tension at the oil/water interface in order to increase oil recovery rates [4][5][6][7]; and (iii) the use of NPs for conformance control such as nanoparticle-stabilized emulsions, and gelation materials to block the easy flow paths [8,9]. All these applications require nanoparticles to transport long distances in reservoir rocks with minimal retention.…”
Section: Introductionmentioning
confidence: 99%
“…The addition or deposition of different nanoparticles could modify the displacing fluid's effective properties such as viscosity [6][7][8] , interfacial tension 9,10 , and dielectric properties 11 ; change the permeability of the rock matrix 12 ; or alter the rock surface wettability 10,13 . In addition, the size-dependent properties (i.e., optical, magnetic, electrical, thermo-physical and interfacial properties) of nanoparticles can be used as sensitive down-hole sensors to target locations that are inaccessible by conventional methods 5,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Polyvinyl alcohol was grafted onto the surface of the nanoparticles and could be sulfonated with a chlorosulfonic acid treatment. It was shown that the lightly sulfonated nanoparticles could be stably dispersed in API brine at 100 °C.…”
Section: Introductionmentioning
confidence: 99%